2011
DOI: 10.1371/journal.pone.0025409
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Tumors Colonized with Bacterial Ferritin-Expressing Escherichia coli

Abstract: BackgroundRecent studies have shown that human ferritin can be used as a reporter of gene expression for magnetic resonance imaging (MRI). Bacteria also encode three classes of ferritin-type molecules with iron accumulation properties.Methods and FindingsHere, we investigated whether these bacterial ferritins can also be used as MRI reporter genes and which of the bacterial ferritins is the most suitable reporter. Bacterial ferritins were overexpressed in probiotic E. coli Nissle 1917. Cultures of these bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…Ftn reporter genes were applied in a wide range of MRI studies including the detection of viral-based gene transfer as a surrogate of gene therapy, monitoring of stem cells and migration of other cells in the context of regenerative medicine for the heart and brain, and monitoring recruitment of cells in cancer [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. As an endogenous protein, which can be used for generating detectable MRI contrast when expressed at physiological levels, Ftn offers the hope for its utilization for detection of transcriptional activation of gene expression, for detection of cell differentiation, and for longitudinal tracking of cell proliferation and migration.…”
Section: Nmr and Mri Studies Of The Ferritin Iron Corementioning
confidence: 99%
“…Ftn reporter genes were applied in a wide range of MRI studies including the detection of viral-based gene transfer as a surrogate of gene therapy, monitoring of stem cells and migration of other cells in the context of regenerative medicine for the heart and brain, and monitoring recruitment of cells in cancer [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. As an endogenous protein, which can be used for generating detectable MRI contrast when expressed at physiological levels, Ftn offers the hope for its utilization for detection of transcriptional activation of gene expression, for detection of cell differentiation, and for longitudinal tracking of cell proliferation and migration.…”
Section: Nmr and Mri Studies Of The Ferritin Iron Corementioning
confidence: 99%
“…Ferritins are ubiquitous iron storage proteins and recent studies have shown that human ferritin can be used as a reporter of gene expression for MRI. 103 Bacteria also encode three classes of ferritintype molecules which Hill et al 104 have recently investigated for their potential as MRI reporter genes. 104 Tumor specific induction of bacterioferritin-expression in colonised murine tumors resulted in contrast changes within the tumors.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…103 Bacteria also encode three classes of ferritintype molecules which Hill et al 104 have recently investigated for their potential as MRI reporter genes. 104 Tumor specific induction of bacterioferritin-expression in colonised murine tumors resulted in contrast changes within the tumors. However, such research on MR imaging genes is still in its infancy and with the exception of the previously discussed studies, its ability to complement bacterial gene therapy imaging is currently limited.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…The bacterial targeting and replication can be imaged in vivo in tumors with a radiolabeled 2′-fluoro-1-beta-d-arabino-furanosyl-5-iodo-uracil (FIAU), which is selectively phosphorylated and trapped in bacteria expressing HSV1-TK. Another study tried to overexpress bacterial ferritin in Escherichia coli to achieve imaging of bacterial colonization in tumors by MRI [38]. These studies using PET or MRI imaging to monitor bacteria in vivo would be needed in the future when bacteria are applied in bigger models or humans.…”
Section: In Vivo Monitoring Of Bacteria With Molecular Imaging Technomentioning
confidence: 99%